Taxonomic and functional diversity of the microbiome in a jet fuel contaminated site as revealed by combined application of in situ microcosms with metagenomic analysis - Hidalgo, K. J.; Teramoto, E. H. [UNESP]; Soriano, A. U.; Valoni, E.; Baessa, M. P.; Richnow, H. H.; Vogt, C.; Chang, H. K. [UNESP]; Valéria, M. Oliveira (Elsevier, 2020)
Natural attenuation represents all processes that govern contaminant mass removal, which mainly occurs via microbial degradation in the environment. Although this process is intrinsic its rate and efficiency depend on multiple factors. This study aimed to characterize the microbial taxonomic and functional diversity in different aquifer sediments collected in the saturated zone and in situ microcosms (BACTRAP®s) amended with hydrocarbons (13C-labeled and non-labeled benzene, toluene and naphthalene) using 16S rRNA gene and “shotgun” Illumina high throughput sequencing at a jet-fuel contaminated site. The BACTRAP®s were installed to assess hydrocarbon metabolism by native bacteria. Results indicated that Proteobacteria, Actinobacteria and Firmicutes were the most dominant phyla (~98%) in the aquifer sediment samples. Meanwhile, in the benzene- and toluene-amended BACTRAP®s the phyla Firmicutes and Proteobacteria accounted for about 90% of total community. In the naphthalene-amended BACTRAP®, members of the SR-FBR-L83 family (Order Ignavibacteriales) accounted for almost 80% of bacterial community. Functional annotation of metagenomes showed that only the sediment sample located at the source zone border and with the lowest BTEX concentration, has metabolic potential to degrade hydrocarbons aerobically. On the other hand, in situ BACTRAP®s allowed enrichment of hydrocarbon-degrading bacteria. Metagenomic data suggest that fumarate addition is the main mechanism for hydrocarbon activation of toluene. Also, indications for methylation, hydroxylation and carboxylation as activation mechanisms for benzene anaerobic conversion were found. After 120 days of exposure in the contaminated groundwater, the isotopic analysis of fatty acids extracted from BACTRAP®s demonstrated the assimilation of isotopic labeled compounds in the cells of microbes expressed by strong isotopic enrichment. We propose that the microbiota in this jet-fuel contaminated site has metabolic potential to degrade benzene and toluene by a syntrophic process, between members of the families Geobacteraceae and Peptococcaceae (genus Pelotomaculum), coupled to nitrate, iron and/or sulfate reduction.
Keywords: Aromatic degradation; BACTRAP®; BTEX contamination; Geobacteraceae; Peptococcaceae